A Self Efficacy Profile of Students Facing the Transition of Online to Offline Learning (Study of Guidance and Counseling Students at PGRI University of West Sumatra, Class Of 2020) - Syuprianto, Resky (Jurnal Riset Ilmu Pendidikan, 2022)
This research is motivated by the presence of students who are confident when taking online lectures rather than face-to-face lectures, there are students who are late in submitting assignments for various reasons. The purpose of this study is to describe the self-efficacy of students facing the transition period of online to offline lectures seen from: 1) Dimensional level (level). 2) Dimensions of strength (Strenght). 3) The general dimension (Generality). This research was conducted using a quantitative descriptive method. The research population was 64 students who were selected by total sampling technique with 64 participants. The instrument used is a questionnaire. Meanwhile, for data analysis using interval and percentage scores. Based on the results of research on student self-efficacy in facing the transition period of online to offline lectures, it can be seen from: 1) student self-efficacy as seen from the indicator dimension of the level of difficulty (level) is in the good category. 2 Student self-efficacy seen from the strength dimension indicator is in the good category. 3) students' self-efficacy seen from the general strength dimension indicators are in the fairly good category. This research is recommended for students to increase self-efficacy by discussing with lecturers or or peers so that students are able to deal with problems that arise during the transition from online lectures to offline lectures.